Product Wheels for Scheduling in the Baking Industry: A Case Study - Alexandria Lee Trattner; Zaza Nadja Lee Herbert-Hansen; Lars Hvam (International Journal of Production Management and Engineering)
This paper illustrates current challenges and suggests solutions within the area of scheduling in the baking industry. The analysis applies the product wheel heuristic approach of King (2009) and tests the production cycles generated using actual sales and production data from a manufacturer of frozen baked goods. The product wheel method showed to be a suitable method for application at the baked goods manufacturer and generated a 23% reduction in setup and inventory cost at the case company. Despite the benefits, the product wheel method proved difficult to apply in a high variety setting, where an operations research model may have achieved more significant results.